Character Education Based on Javanese Culture in Surakarta Palace at Kasatriyan Elementary School, Surakarta - Faturohim, Ikhsan; Triyanto, Triyanto; Daryanto, Joko (Social, Humanities, and Educational Studies (SHES): Conference Series, 2024)
The research aims to describe the management of character education based on Javanese culture of Surakarta Kasunanan Palace in Kasatriyan Surakarta Elementary School, with a descriptive qualitative research type, in the form of a single case study strategy. Data collection techniques used participatory observation, in-depth interviews, documentation, and field notes. The results of the study concluded that the management of Javanese culture-based character education of Surakarta Palace in the form and implementation of the program. In terms of program form based on: The vision, mission and goals of the school, that the school implements Javanese culture-based education. Through its vision, SD Kasatriyan Surakarta wants to produce students who are knowledgeable, faithful, devoted to God Almighty and have noble character. Through its objectives, it wants to preserve regional culture through Local Content of Regional Language and it is expected that 75% of students are able to speak Javanese properly and correctly. In the school's mission, which is to promote education and establish partnerships with related agencies in order to prepare quality resources for common welfare. The teaching program through character education integrates Javanese culture, such as intracurricular programs. Extracurricular programs: karawitan, dranband and kulintang. Habituation teaching programs, such as: neatness of dress, good manners, shaking hands, speaking Javanese to communicate, especially during Javanese language lessons.